United Nations E-Government Survey 2020 - United Nations (United Nations, 2020)
The Survey assesses global and regional e-government development through a comparative rating of national government portals relative to one another. It is designed to provide a snapshot of country trends and relative rankings of e-government development in the implementation of the Sustainable Development Goals. It presents trends and relative rankings of e-government development across 193 Member States through a quantitative composite index, the E-Government Development Index (EGDI), with three separate components - the Online Service Index (OSI), Telecommunication Infrastructure Index (TII), and Human Capital Index (HCI). Includes addendum on COVID-19 (coronavirus) response.